Exploring economic and health interventions to support adolescents’ resilience and coping in mining communities: A scoping review - Chidwick, H.; Randolph-Koranteng, N.; Osei, L.; et al. (The Extractive Industries and Society, 2023)
Economic and social disruptions, such as the global COVID-19 pandemic, heighten the vulnerability of adolescents. These disruptions exacerbate health and economic inequities which are further compounded in informal labour settings such as the mining sector. Therefore, strengthening adolescent resilience and coping are crucial for well-being and equitable health outcomes. However, there is a limited comprehensive literature that synthesizes adolescent resilience interventions, especially in mining communities. This study presents a scoping review, following Arksey & O’Malley’s (2005) framework, to map existing literature on interventions for adolescent resilience in mining communities. Relevant studies were identified from academic journals and grey literature published between 2012 and 2022. Of the 1286 studies screened, 13 were retained for final analysis. Literature showed that common economic resilience interventions included policy-level advocacy and activism, and predominant health interventions focused on sexual and reproductive health including, HIV counselling, screening, and testing, targeting both individual and community-level change in mining communities. The findings emphasize the necessity for interventions to adopt multi-level, multi-sectoral, and multi-stakeholder approaches, while mainstreaming gender. Future research should prioritize intersectional, gender transformative and community-based interventions to strengthen adolescent resilience in mining communities and advance health equity and rights amongst this last-mile population.
Research Article
Keywords: Last mile; Adolescent; Mining; Resilience